Study of the microbiological activity in the agrocenosis from Crisurilor Plain - Onet, Aurelia; Onet, Cristian (Acta Agraria Debreceniensis, 2013)
The seasonal variations of soil microorganisms depend on changes in the soil chemical properties and the microbiological processes of soil are determined in main by different cropping systems, soil management and season. Investigation of the microbiological properties of a haplic luvisol, under different cultivation conditions showed that anthropogenic factors such as fertilization and treatments with pesticides was favourable for certain microorganisms while others were inhibited by these factors. In order the quantitative occurence of microorganism was aerobic mesophilic heterotrophs (105–107 cellsxg-1 dry matter soil) were followed by Actinomycetes, yeast and mould (103–106 cellsxg-1 dry matter soil), nitrogen fixing bacteria (102–105 cellsxg-1 dry matter soil) and nitrifying bacteria (10-1–103 cellsxg-1 dry matter soil). The highest values of aerobic mesophilic heterotrophs were found in cropland and undisturbed meadow of haplic luvisol. Actinomycetes are more developed in undisturbed soils than in the cultivated soils. The number of yeast and mould was high in the apricot tree orchard, and Azotobacter and nitrifying bacteria were identified in a small number in all the soil variants studied. Among the total number of aerobic microorganisms, pH and humus content statistically proved relationship was established. Total number of yeast and mould depends on the proportion of 10.89% by moisture content and pH. The numerical presence of Azotobacter depends in a proportion of 9.6% by the ammonia nitrogen content and pH variations. The numerical presence of nitrifying bacteria depends in a proportion of 1.69% by the nitric nitrogen content and humus content variation.